Strong Lewis and Brønsted Acidic Sites in the Borosulfate Mg3[H2O→B(SO4)3]2. Issue 19 (30th March 2021) - Netzsch, Philip; Stroh, Regina; Pielnhofer, Florian; Krossing, Ingo; Höppe, Henning A.
Abstract: Borosulfates provide fascinating structures and properties that go beyond a pure analogy to silicates. Mg3 [H2 O→B(SO4 )3 ]2 is the first borosulfate featuring a boron atom solely coordinated by three tetrahedra. Thus, the free Lewis acidic site forms a Lewis acid–base adduct with a water molecule. This is unprecedented for borosulfate chemistry and even for borates. Quantum chemical calculations on water exchange reactions with BF3 and B(C6 F5 )3 revealed a higher Lewis acidity for the borosulfate anion. Moreover, proton exchange reactions showed a higher Brønsted acidity than comparable silicates or phosphates. Additionally, Mg3 [H2 O→B(SO4 )3 ]2 was characterised by X‐ray diffraction, infrared spectroscopy, thermogravimetric analysis, and density functional theory (DFT) calculations. Abstract : The ever‐expanding chemistry of borosulfates is enriched by the novel borosulfate Mg3 [H2 O→B(SO4 )3 ]2 featuring an unprecedented Lewis acid–base adduct of water to the anion [B(SO4 )3 ] 3− . Isodesmic exchange calculations revealed high Lewis and Brønsted acidity, opening new insights and perspectives for this fascinating silicate‐analogous material class.